A Study of the Toxic Effect of Polystyrene Microplastics on Oxygen Consumption in a Freshwater Fish Heteropneustes fossilis - Yadav, Ramesh; Paul, D. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Microplastics (MPs) are new emerging environmental pollutants in aquatic environments that attract widespread attention due to their small size and potential toxic impacts on aquatic organisms. In the present study, we investigated the toxic effects of short-term exposure to polystyrene microplastics at different doses on the oxygen consumption of Heteropneustes fossilis. The fish, after acclimatization, was exposed to polystyrene microplastics at 10.79µg/L, 17.98 µg/L, and 35.96 µg/L for 12 hours.The control group (first group) of fishes showed oxygen consumption of 72.86± 5.05 mg/kg/hr, the second group 69.21±3.64 mg/kg/hr, the third group 57.64±4.04, and the fourthgroup 51.92±4.95 in the closed chamber while 38.99 ± 2.34 mg/kg/hr, 33.47± 1.28 mg/kg/hr, 33.38± 2.40 mg/kg/hr, 29.36± 1.24 mg/kg/hr in open chamber. The decreasing trend of oxygen uptake in the fish was found in both cases after intoxication. The trend may be due to stress conditions of fish correlated with low RBC values and hemoglobin levels due to microplastic intoxication. Alterations in oxygen consumption may be due to respiratory distress due to impaired oxidative metabolism.